2015
DOI: 10.1039/c5tc02956b
|View full text |Cite
|
Sign up to set email alerts
|

Substitution of silicon within the rhombohedral boron carbide (B4C) crystal lattice through high-energy ball-milling

Abstract: Boron carbide (B 4 C) is a ceramic with a structure composed of B 12 or B 11 C icosahedra bonded to each other and to three(C and/or B)-atom chains. Despite its excellent hardness, B 4 C fails catastrophically under shock loading, but substituting other elements into lattice sites may change and possibly improve its mechanical properties. Density functional theory calculations of elemental inclusions in the most abundant polytypes of boron carbide, B 12 -CCC, B 12 -CBC, and B 11 C p -CBC, predict that the pref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
22
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 62 publications
6
22
0
Order By: Relevance
“…The peak at 283.1 eV shows bonding interactions of carbon and silicon. This fact is again confirmed by a peak around 100.6 eV in the Si 2p region (Figure g) . The peaks exhibited with binding energies at 284.4 and 286.6 eV are assigned to ferrocenyl carbons and carbenic carbon (C 2 carbon of benzimidazolium ring) bonded with Cu respectively .…”
Section: Resultssupporting
confidence: 52%
“…The peak at 283.1 eV shows bonding interactions of carbon and silicon. This fact is again confirmed by a peak around 100.6 eV in the Si 2p region (Figure g) . The peaks exhibited with binding energies at 284.4 and 286.6 eV are assigned to ferrocenyl carbons and carbenic carbon (C 2 carbon of benzimidazolium ring) bonded with Cu respectively .…”
Section: Resultssupporting
confidence: 52%
“…Silicon has never been successfully incorporated to such a large extent despite multiple attempts [8][9][10][11][12][13]. The maximum solubility of Si in boron carbide, experimentally achieved, is reported to be 2.5 ±0.5 at.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…Efforts to minimize amorphization have mostly been focused on doping boron carbide with foreign atoms and forming composites. DFT analyses [39] for (B 12 )CBC and (B 12 )CCC revealed that Be, Mg, Al and Si preferred chain centers for substitution while N, P and S preferred chain ends; for (B 11 C p )CBC, Si favored polar icosahedral sites. Experimentally, doping with silicon in the icosahedra has roughly doubled the pressure required for amorphization to 67 GPa [40].…”
mentioning
confidence: 98%